Characterization of Tunisian pomegranate ( Punica granatum L.) cultivars using amplified fragment length polymorphism analysis - Jbir, Rania; Hasnaoui, Néjib; Mars, Messaoud; Marrakchi, Mohamed; Trifi, Mokhtar (Scientia horticulturae, 2008)
The amplified fragment length polymorphism (AFLP) analysis of DNA was used to characterize 34 pomegranate cultivars. By using a combination of six primers, a total of 327 markers were scored with a mean of 57.5. The high percentage of polymorphic bands (ppb) of 94.7 and the resolving power ( R p) collective rate value of 129.14 were scored. Data proved that the tested primers were informative to discriminate among cultivars and to survey the genetic diversity in this fruit crop. It has been assumed that the local pomegranate germplasm is characterized by a typically continuous genetic diversity. The derived dendrogram proved that cultivars are clustered independently from their geographical origin and their denomination. In addition, AFLP permitted the generation of a nearly unlimited number of molecular markers that are reliable in differentiating the cultivars and/or the polyclonal varieties.